Analisis Sifat Magnet Dan Mekanik Pada Permanent Bonded Magnet Pr-Fe-B Dengan Matriks Bakelit - Tian Havwini (Saintia Fisika, 2013)
Bonded magnet is composite magnet material made by mixing magnetic powder with non-magnetic binder. Bonded permanent magnet Pr-Fe-B with bakelite matrix made manually by mixing powder of Praseodymium Iron Boron (Pr-Fe-B) commercial MQP type 16-7 with binder by using mortar. The composition of bakelite powder was varied at 2, 4, 6 and 8 weight% respectively from each 8 gram total mass. Then this mixture was pressed by using dry compression moulding method with pressure 5 ton and dried at 150ºC for 2 hours. Magnetic properties were characterized by measuring flux density using Gaussmeter and hysteresis loop by using Permagraph. While compressive strength was characterized using Universal Testing Machine and hardness was characterized using Brinell hardness method. The results showed that increasing portion of binder would increase hardness and compressive strength qualitatively but decreased the magnetic properties. The best magnetic properties value obtained for the 2 weight% composition of bakelite and the value of flux density = 1186 gauss, Br = 6.63 kG, HcJ = 6.962 kOe, BHmax = 7.98 MGOe, hardness = 42.2 BHN and compressive strength = 101.4 MPa.